Eyelid abscess as an initial manifestation of whipple’s disease: a case report and comprehensive literature review - Ashwaq Yahya Asiri; Khawlah A. Alzaben; Yousef A. AlOtaibi; Humoud Mohammad AlOtaibi; Hind Manaa Alkatan (BMC Ophthalmology)
Abstract Background Whipple’s disease, caused by Tropheryma whipplei, is a rare chronic infection predominantly affecting the gastrointestinal tract. Ocular involvement is uncommon, and periorbital manifestations are exceedingly rare. This case report highlights a unique presentation of Whipple’s disease as an eyelid abscess in a patient with type 1 diabetes mellitus. Case presentation A 38-year-old male with poorly controlled type 1 diabetes mellitus presented with a two-weeks history of progressive swelling in the left upper eyelid. The swelling initially appeared three months prior and was associated with mild pain. Clinical examination revealed a large, erythematous, bluish, and non-tender swelling in the left upper eyelid, causing mechanical ptosis. Additional lesions were noted on the scalp and abdomen. Imaging showed a well-circumscribed fluid-filled lesion in the left upper eyelid. A tissue sample was taken for culture and biopsy during surgical drainage. The histopathology showed foamy macrophages with Diastase-resistant intracytoplasmic organisms that were further demonstrated by Gram stain confirming the diagnosis of Whipple’s disease. Conclusion This case illustrates a rare presentation of Whipple’s disease manifesting as an eyelid abscess in a diabetic patient. The diagnosis was confirmed through histopathological examination, emphasizing the importance of considering Whipple’s disease in the differential diagnosis of atypical ocular presentations.